2011
DOI: 10.1074/jbc.m111.234583
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bulk Water in Hydrolysis of the Rhodopsin Chromophore

Abstract: Rhodopsin (Rho) is a prototypical G protein-coupled receptor that changes from an inactive conformational state to a G protein-activating state as a consequence of its retinal chromophore isomerization, 11-cis-retinal 3 all-trans-retinal. The photoisomerized chromophore covalently linked to Lys 296 by a Schiff base is subsequently hydrolyzed, but little is known about this reaction. Recent research indicates a significant role for tightly bound transmembrane water molecules in the Rho activation process. Atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 38 publications
8
60
0
Order By: Relevance
“…For formyl peptide receptor 1 (FPR 1 ) and opioid receptors (ORs), using microsecond MD simulations, we showed that the influx of water molecules occurs towards the allosteric site, which is different from that in the human sphingosine-1-phosphate receptor 1 (S1PR 1 ) 30 . Jastrzebska et al 3 reported that water molecules can reach the opsin binding region from the intracellular side during the retinal isomerization in Rho, which is also seen in our MD simulations of Rho. These observations imply that there are two possible water penetration routes.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…For formyl peptide receptor 1 (FPR 1 ) and opioid receptors (ORs), using microsecond MD simulations, we showed that the influx of water molecules occurs towards the allosteric site, which is different from that in the human sphingosine-1-phosphate receptor 1 (S1PR 1 ) 30 . Jastrzebska et al 3 reported that water molecules can reach the opsin binding region from the intracellular side during the retinal isomerization in Rho, which is also seen in our MD simulations of Rho. These observations imply that there are two possible water penetration routes.…”
Section: Resultssupporting
confidence: 66%
“…For G-protein-coupled receptors (GPCRs), which form the largest class of membrane proteins transmitting extracellular signals across the plasma membrane, internal water molecules have been proposed to play an important role for receptor activation but mechanistic models remain speculative 2 . Previous studies revealed that water molecules from the cytoplasmic region of rhodopsin (Rho) are involved in the hydrolytic release of retinal upon Rho activation by light 3,4 . Crystal structures of Rho and the beta-2 adrenergic receptor (b 2 AR) revealed further details.…”
mentioning
confidence: 99%
“…Functional integrity of the preparation was examined spectrophotometrically by measuring the Rh6mr spectrum both in the dark and after a light stimulus. The orientation of Rh6mr or Rh in proteoliposomes was confirmed by Asp-N endoproteinase digestion (39,47), which cleaves opsin specifically between Gly329 and Asp330 in the C-terminal tail (48).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a solution of commercially available soybean phospholipids (asolectin; Sigma-Aldrich) in buffer containing 10 mM MES (pH 5.9), 100 mM NaCl, and 1% n-nonyl-β-Dglucopyranoside (NG) was mixed with purified Rh6mr or Rh. The molar ratio of asolectin [assumed molecular mass, 760 (46)] to Rh6mr or Rh was 200:1 (39,47). The protein-lipid suspension was kept at 20°C for 2 h, followed by dialysis against buffer containing 10 mM MES (pH 5.9) and 100 mM NaCl (2,000-fold excess) at 4°C in the dark for 48 h with four buffer changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation